Hubungan Pengetahuan dengan Perilaku Ibu Hamil Usia Reproduksi Sehat dengan Pemeriksaan Triple Elliminatiom Skrining (HIV, Sifilis, dan Hepatitis B) - Kahar, Fitriani (Poltekkes Kemenkes Semarang, 2025)
Pregnant women are one of the populations at risk of contracting Sexually Transmitted Infections (STIs) such as HIV, Syphilis, and Hepatitis B. The prevalence of HIV/AIDS transmission from mother to child is 20-50% where 5-10% occurs during pregnancy. Syphilis transmission is 69-80% and Hepatitis B transmission is more than 90% with the potential for transmission during pregnancy and childbirth being very high. Based on the Regulation of the Minister of Health of the Republic of Indonesia, regulation No. 52 of 2017 concerning the Elimination Program for Transmission of Human Immunodeficiency Virus, Syphilis, and Hepatitis B from Mother to Child or often called